للتنبؤ بحجم العمليات القيصرية في مستشفى البتول في مدينة الموصل للعام 2002-2006BOX-JENKINSتوفيق احد نماذج - منى منير احمد (PROSPECTIVE RESEARCHES, 2023)
Today Cesarean Operation is considered one of the most common and widespread operation in obstetric hospitals especially the lower segment operation. The increase use of this procedures became one of the most important problems that need to study the size of this problem. The aim of the study is to combine one of the models of BOX-JENKINS for time series for Cesarean Section that take place in Al-Batool teaching hospital Between 2002-2006 which was equal to 19493 Cesarean Section. The data were collected during 60 months in which the series were unstable. In this study, we take the Cosine and lag1 differences of the data to make it stable around the variance and the mean. The present study shows that the suitable model for this series were AR(1) model through drawing the autocorrelation and the partial autocorrelation function. For more confidence of chosen model according to BOX-JENKINS model, we calculate BIC(M) scale for all models used to choose the best one using the most modern statistical program MINITAB-13).